Cephalalgia heterotopica: a case series of lower half face migraine - Bordini, Carlos Alberto; Silva Junior, Hilton Mariano da (Headache Medicine, 2022)
IntroductionMigraine is a common and very disabling neurological disease. It typically causes severe throbbing pain or a pulsing sensation, usually on one side of the head. It's often accompanied by nausea, vomiting, and extreme sensitivity to light and sound. According to the definition of headache, the pain should be located in the head or in the face above the orbitomeatal line. Beyond this classical view, recent evidence has shown that it could be an arbitrary boundary, and other clinical features can prevail during the diagnosis process. ObjectiveThis consecutive case series study aimed to report clinical features, treatment, and outcome of 5 patients with a lower-half facial presentation of migraine. Materials and MethodsCase series of our Headache Clinic.  Data disclosure was authorized by the patients through an informed consent form.  ResultsOf the 5 patients, 3 were women and 2 were men. Mean age was 34, 6 (13-56 years). The mean age of symptoms onset was 15,2 (11-29 years).All patients described a throbbing, moderate to severe pain in the malar area. Four patients reported frequent phonophobia and photophobia accompanying pain attacks. One patient reported great relief of pain with rizatriptan and another with sumatriptan. Preventive treatment with pizotifen, propranolol, flunarizine, amitriptyline, divalproex sodium, and pregabalin was useful. All patients underwent extensive dental and otolaryngological evaluation and treatment, which were worthless.  ConclusionMigraine orofacial presentation is a diagnostic challenge. Proper recognition of these cases not only prevents unnecessary examination and treatment trials but directly benefits the patients since effective treatment is already available. A proper case definition of this rare clinical presentation may provide new insight into our understanding of the migraine mechanisms.  Keywords: Facial pain, Migraine, Lower half-face migraine.